A contribution to the study of the cold wire TIG process in the flat, horizontal and overhead position with new torch designs and wire feed methodologies. Issue 6 (3rd June 2017) - Díaz, Victor Vergara; Cortes, John Michea; Alvarez, Abdón Espinosa
Abstract: This line of research aims to improve current procedures in the welding of boiler tubes, where manual welding processes are used and the quality of the welded joints depend exclusively on the welder's skill. In this connection, what is proposed is to effect repairs with a more productive welding process called cold wire TIG with mechanized feed of cold wire, with the aim of achieving improvements in weldment quality and repeatability. The weld beads were assessed according to surface appearance, morphology, degree of dilution and convexity index. Tests were carried out with two wire guides (20° and 48°) for verifying the influence of the angle of introduction of the wire in the arc. The results indicate a considerable increase in productivity of the TIG process with mechanized wire feed, when the guide developed is employed with a wire entry angle of 20°, approaching the deposition rate obtained with the MIG/MAG process for the same wire diameter. Two configurations of wire feed could be tested: continuous and pulsed. The results showed that the pulsed wire feed configuration proposed was applied successfully in all positions, ensuring repeatability, process stability and stability of the molten pool.